Analisis Kinerja Simpang Tiga Bersinyal Jalan Raya Sesetan, Jalan Pulau Buton dan Jalan Raya Diponegoro, Denpasar Selatan - Putu Eka Suartawan Suartawan; Adozindo Sebastiao Gama Vicente (Universitas Pendidikan Nasional, 2022)
Denpasar City is the capital city of Bali which has a very high population. It can be seen that the population of Denpasar City is 726,599 people [1]. Sanglah intersection is a signalized intersection with three arms connecting Jalan Raya Sesetan, Jalan Pulau Buton, and Jalan Raya Diponegoro. The environmental condition at the intersection is a commercial area that is marked by the presence of shops around the Sanglah intersection. Therefore, it is often delayed because the volume of vehicles passing through the intersection is quite dense, so the performance of the intersection is less than optimal. So it is necessary to analyze the performance of the intersection using the 1997 Indonesian Road Capacity Manual Method. From the data collection and processing results using the 1997 Indonesian Road Capacity Manual Method, the traffic volume on Jl. Raya Sesetan is 1304.7 smp/hour, Jl. Raya Diponegoro is 1204 smp/hour, Jl. Buton Island is 628.5 smp/hour. The capacity is 1354 smp/hour, 1250 smp/hour, 652 smp/hour. Degree of saturation 0.96, signal time 151 seconds, queue length 145 m, 131 m, 171 m, delay 81.65 sec/smp, 123.98 sec/smp, 133.58 sec/smp. Based on the analysis that has been done, the degree of saturation at the intersection is 0.96, exceeding the standard value of the degree of saturation according to the 1997 Indonesian Road Capacity Manual method, which is 0.85. To overcome this, one alternative design is a green time design for each approach, specifically the south and west approaches. This alternative will improve the performance of the intersection.